Comportamento do implante contendo bone morphogenetic protein (bmp) associado ao plasma rico em plaquetas na reparação de fraturas orbitárias - Da Silva Ferraz, Fábio Henrique [UNESP]; Schellini, Silvana Artioli [UNESP]; Pellizzon, Cláudia Helena [UNESP]; De Campos Schellini, Ricardo [UNESP]; Padovani, Carlos Roberto [UNESP] (My University, 2006)
Purpose: This study intends to evaluate BMP (Bone Morphogenetic Protein) implant and BMP implant plus PRP (Platelet Rich Plasma) in rabbit orbital fractures, searching for tissue reaction, by radiological and morfometrical analysis. Methods:Third six white rabbits were submitted to orbital floor fracture and distributed in three groups: G1, with rabbits receiving a plate containing decalcified bone matrix and BMP; G2, with rabbits receiving the implant with BMP wrapped by PRP; G3, the control group where it was made the fracture only. The animals were evaluated radiologically after surgery and at sacrifice time in 7, 30, 90 and 180th day after surgery. After sacrifice, a block containing the right orbital tissue was extracted and prepared to morphological and morphometrical analysis. Results: An intensive linfomononuclear inflammatory reaction was observed at 7th day in G1 e G2, witch decreased after the 30th day; mesenchimal cells, osteoblasts, new bone and progressive cavitation of the implant were also observed, besides signs of calcium deposition by radiological study. In the control group fibrosis at the site of fracture was identified only. Conclusion: BMP seemed a good orbital implant producing new bone at the implant site and correcting bone defect.There was not observed acceleration of osteoinduction when the implant was associated with PRP.
Bone morphogenetic protein (bmp) implant associated with platelet rich plasma in orbit fracture repair - experimental study
Keywords: Blood platelets; Bone morphogenetic proteins/therapeutic use; Bone remodeling; Orbital fractures; Plasma